Posterior Urethral Valves and Fertility: Insight on Paternity Rates and Seminal Parameters - Marcello Della Corte; Simona Gerocarni Nappo; Antonio Aversa; Sandro La Vignera; Francesco Porpiglia; Cristian Fiori; Nicola Mondaini (Diseases)
Background: Posterior urethral valves (PUVs) represent the most common cause of male congenital lower urinary tract obstruction, often responsible for renal dysplasia and chronic renal failure. Despite recent improvements in patients’ outcomes thanks to prenatal ultrasound early diagnosis, PUVs can still impact sexual function and fertility. This study aims to review the available evidence on fertility in PUV patients, examining paternity rates and semen parameters. Methods: A review was conducted of the PubMed, Cochrane, Scopus, and Embase databases. Studies focusing on fertility and paternity outcomes in PUV patients were selected, including case reports, case series, and retrospective and prospective studies. Results: A total of 15 studies met the inclusion criteria. The review revealed that PUV patients often exhibit compromised semen parameters, including low sperm count, reduced motility, and abnormal morphology, as well as alterations in seminal plasma. PUV diagnoses are common in adults exhibiting infertility and ejaculation disorders, suggesting PUVs cannot be considered only a pediatric disease. Paternity rates among PUV patients were rarely reported in extenso, hampering the correct assessment of the overall medium paternity rate and its comparison with that of healthy individuals. Lastly, seminal parameters were assessed in a minimal cohort of patients, therefore, they could not be considered representative. Conclusions: Fertility and seminal parameters in PUV patients represent an under-investigated area. PUVs can variably and non-univocally affect fatherhood, and they may be associated with compromised semen quality. Early intervention and long-term follow-up are essential to address potential fertility issues. Future research should focus on developing targeted strategies to preserve and enhance fertility in this patient population.